The Characteristics on Career Development and Loyalty at the Higher Education: An Educational Perspective - Santalia, Indo; Syafaruddin, Baso; Hasriadi, Hasriadi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study examines the influence of faculty characteristics on career development and loyalty at IAI As'adiyah Sengkang, focusing on perspectives from education and da’wah. The research was conducted using three data collection methods: observation, interviews, and documentation, with faculty members serving as primary data sources. Additional informants, including leadership and staff, were consulted to enrich the findings. The study utilized a descriptive-qualitative data analysis approach, employing inductive, deductive, and comparative techniques. Results indicate that faculty characteristics significantly contribute to career advancement and loyalty within the institution. Notably, many faculty members have progressed in their careers, securing academic positions, achieving higher academic ranks, and obtaining certifications. From an educational and da’wah perspective, the study reveals that faculty characteristics align with career development, as seen in the increasing number of faculty members pursuing further studies in Islamic Education with a focus on Da’wah Technology at the graduate level. Furthermore, some faculty members are advancing their education by pursuing doctoral studies. The methods used by faculty to advance their careers adhere to Islamic principles, reflecting a strong integration of professional growth and religious values. This research underscores the important role faculty characteristics play in fostering career development and loyalty in an academic setting.